Fiber-optic bend sensor using LP21 mode operation - Fan, Yuqiang. (2013)
A novel fiber-optic bending sensor based upon the propagation of LP21 mode is demonstrated. The sensor, comprised of an S-bend fiber on an elastic film, measures LP21 mode specklegram rotation, which increments linearly with bending angle by the stress-optic effect. The sensor is capable of experimentally achieving a sensitivity as high as 4.13 rad/m−1. The theoretical analysis of the sensor, which is a combination of fiber coupled-mode theory and elastic-optic theory, validates the accuracy of the sensor. The sensor is also shown to be temperature-immune, and can detect both bending direction and bending angle with a large dynamic range. Furthermore, the sensor implementation incorporates inexpensive single-mode fiber at 650 nm for few-mode operation, enabling low-loss transmission and compatibility with existing interfaces.